Carotenoid profile in grapes related to aromatic compounds in wines from Douro region - Oliveira, Carla (2011)
The aim of this work was to characterize 8 representative grape varieties of the Douro Region using the carotenoid profile as it relates to aromatic compounds in the respective wines. Some other analyses, such as the determination of sugar, probable alcohol, pH, and total acidity, were also performed in an attempt to understand in which way the evaluated characteristics influenced by grape variety could contribute to the wine aroma. For the 3 y of the study, grape varieties with higher concentrations of carotenoids (Touriga Fêmea, Tinta Amarela, and Tinta Barroca) have lower values of free norisoprenoids, even with exceptions (Touriga Fêmea). Conversely, grape varieties with lower concentrations of carotenoids (Touriga Nacional, Sousão, and Tinto Cão) appear to have higher contents of free norisoprenoids, namely b-ionone for Touriga Nacional and vitispirane and 1,1,6-trimethyl-1,2- dihydronaphthalene (TDN) for Sousão and Tinto Cão. Touriga Nacional, followed by Touriga Fêmea, was the wine variety with the highest values of total free terpenols (linalol, a-terpineol, nerol, and geraniol), the presence of which is responsible for the floral aroma.